Prolegomena on Metre and Textual History of the Rgveda. By Vytis Vidūnas - Oldenberg, Hermann (Acta Orientalia Vilnensia, 2005)
Center of Oriental Studies, Vilnius UniversityHERMANN OLDENBERG. Prolegomena on Metre and Textual History of the »gveda, trans. into English V. G. Paranjape and M. A. Mehendale (from Metrische und textgeschichtliche Prolegomena, Berlin, 1988), Delhi:Motilal Banarsidass, 2005, xiv, 507. ISBN: 81-208-0986-6, Rs. 895